An ER‐peroxisome tether exerts peroxisome population control in yeast. (30th July 2013) - Knoblach, Barbara; Sun, Xuejun; Coquelle, Nicolas; Fagarasanu, Andrei; Poirier, Richard L; Rachubinski, Richard A
<x xml:space="preserve">Abstract</x> Eukaryotic cells compartmentalize biochemical reactions into membrane‐enclosed organelles that must be faithfully propagated from one cell generation to the next. Transport and retention processes balance the partitioning of organelles between mother and daughter cells. Here we report the identification of an ER‐peroxisome tether that links peroxisomes to the ER and ensures peroxisome population control in the yeast Saccharomyces cerevisiae. The tether consists of the peroxisome biogenic protein, Pex3p, and the peroxisome inheritance factor, Inp1p. Inp1p bridges the two compartments by acting as a molecular hinge between ER‐bound Pex3p and peroxisomal Pex3p. Asymmetric peroxisome division leads to the formation of Inp1p‐containing anchored peroxisomes and Inp1p‐deficient mobile peroxisomes that segregate to the bud. While peroxisomes in mother cells are not released from tethering, de novo formation of tethers in the bud assists in the directionality of peroxisome transfer. Peroxisomes are thus stably maintained over generations of cells through their continued interaction with tethers.